ChemInform Abstract: Enantioselective Carbene Cascade: An Effective Approach to Cyclopentadienes and Applications in Diels—Alder Reactions. Issue 40 (September 2016) - Wang, Xiangbo; Zhou, Yunfei; Qiu, Lihua; Yao, Ruwei; Zheng, Yang; Zhang, Cheng; Bao, Xiaoguang; Xu, Xinfang
Abstract: An asymmetric carbene cascade reaction, which proceeds through a carbene/alkyne metathesis and a formal [3+2] cycloaddition and converts alkynyl‐tethered enol diazoacetates to chiral bicyclic cyclopentadienes, is presented.